KEAMANAN INTERNASIONAL KOLEKTIF DAN PERAN ORGANISASI REGIONAL - Riyanto, Sigit (TANJUNGPURA LAW JOURNAL, 2021)
Abstract Following the end of the Second World War, international community adopted International Collective Security system and institutionalized in the United Nations Charter.  This system considered as the new international security architecture in which the United Nations Security Council has the responsibility to design and implement accordingly in the framework of preserving international peace and security in line with the purposes and principles of the United Nations. Interestingly Chapter VIII of the United Nations Charter also provides constitutional basis for the involvement of regional organizations in the maintenance of international peace and security. As regional organizations are very diverse and not all of them are having the same posture, structure, resources and capability in the context of dealing with the challenges related to international peace and security, this article aimed at analysed the role and position of the regional organization in supporting the implementation of International Collective Security system. The first part traces the concept of International Collective Security embodied in the UN charter. The second part assesses the current engagement and role of regional organization in Europe, with special attention directed to The North Atlantic Treaty Organization (NATO). The third part critically examines the current legal arrangement in Asia with particular attention given to the Association of South-East Asian Nations (ASEAN). In conclusion the capability of NATO in supporting the implementation of the International Collective Security system upon the authorization of the UN Security Council is widely recognized by the international community. However, the overstepping of the mandate may have a negative effect in the future, particularly on the credibility of the responsibility to protect in the context of gross human rights violations. In such a context, to became a more effective player in the future, ASEAN needs to make further adjustment.Abstrak Salah satu penanda penting pembentukan organisasi internasional PBB adalah diterima dan dilembagakannya sistem Keamanan Internasional Kolektif dalam Piagam PBB. Sistem Keamanan Internasional Kolektif merupakan arsitektur keamanan internasional yang baru yang diterima masyarakat internasional paska Perang Dunia Kedua. Dalam sistem ini Dewan Keamanan PBB memiliki tanggungjawab utama untuk merancang dan mengimplementasikan sesuai dengan maksud dan tujuan pembentukan PBB. Faktanya, Piagam PBB Bab VIII juga memberikan landasan konstitusional bagi kerangka Kerjasama regional dalam rangka melaksanakan upaya-upaya perdamaian dan keamanan internasional. Mengingat kini terdapat berbagai organisasi internasional dengan beragam struktur, kapasitas, dan kapabilitas dalam upaya menangani masalah-masalah perdamaian dan keamanan internasional; tulisan ini dimaksudkan untuk mengkaji posisi dan peran organisasi regional dalam mendukung implementasi sistem keamanan internasional kolektif. Bagian pertama mengkaji institusionalisasi Keamanan Internasional Kolektif dalam Piagam PBB. Bagian kedua mengkaji keterlibatan organisasi regional di Eropa, dengan perhatian utama terhadap NATO. Bagian ketiga mengkaji secara kritis kerangka kerjasama regional di Asia, dengan perhatian utama kepada ASEAN. Faktanya kapasitas NATO dalam mendukung implementasi sistem keamanan internasional kolektif telah diakui dan mendapat apresiasi masyarakat internasional. Namun demikian, kegiatan yang melampaui mandat yang diberikan kepadanya telah menimbulkan kekhawatiran tentang akuntabilitas dan kredibilitasnya untuk memberikan perlindungan mana kala terjadi pelanggaran HAM di masa depan. Dalam konteks yang sama ASEAN perlu melakukan transformasi signifikan untuk dapat berperan lebih efektif dalam tatakelola internasional di masa depan.